2023
DOI: 10.24036/jep/vol7-iss1/728
|View full text |Cite
|
Sign up to set email alerts
|

Applying Meaningful Learning (NGL and Game) to Improve Students' Scientific Concept Understanding and Scientific Literacy in Reproductive System Material

Andri Rudi Yanto,
Yuni Pantiwati,
Avina Ridatul Saputri
et al.

Abstract: Scientific concept understanding and scientific literacy are essential for students to have. Excellent scientific concept understanding and scientific literacy make it easier for students to learn new material and solve problems they face. This study aims to increase junior high school students' scientific concept understanding and scientific literacy in reproductive system materials by applying meaningful learning with NGL games. The design used in this research is Classroom Action Research (CAR) by Kammi and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Students have not been able to engage in the mastery of thinking and acting using scientific methods to find out and solve problems, known as scientific literacy skills (Huryah et al, 2017). In fact, it is important to train scientific literacy skills for students as early as possible (Yanto et al, 2023). Students' laziness in reading case studies or problems presented in the questions was also suggested to be the cause of their low problem-solving skills scores.…”
Section: Discussionmentioning
confidence: 99%
“…Students have not been able to engage in the mastery of thinking and acting using scientific methods to find out and solve problems, known as scientific literacy skills (Huryah et al, 2017). In fact, it is important to train scientific literacy skills for students as early as possible (Yanto et al, 2023). Students' laziness in reading case studies or problems presented in the questions was also suggested to be the cause of their low problem-solving skills scores.…”
Section: Discussionmentioning
confidence: 99%